Rapid generation of specific protective immunity to Francisella tularensis. - Elkins, K L (1992)
Mice inoculated either subcutaneously (s.c.) or intradermally (i.d.) with a sublethal dose of Francisella tularensis LVS are immune to a lethal intraperitoneal (i.p.) or intravenous (i.v.) challenge of LVS. Here, we show that this immunity developed quite rapidly: mice given a sublethal dose of live LVS s.c. or i.d. (but not i.v.) withstood lethal i.p., i.v., or i.d. challenge as early as 2 days after the initial inoculation, despite the presence of bacterial burdens already in tissues. The magnitude of this early protection was quite impressive. The i.p. 50% lethal dose (LD50) in naive C3H/HeN mice was only 2 bacteria, while the i.p. LD50 in mice given 10(4) LVS i.d. 3 days previously was 3 x 10(6) bacteria. Similarly, the i.v. LD50 in C3H/HeN mice shifted from 3 x 10(2) in naive mice to 5 x 10(6) in primed mice within 3 days after i.d. LVS infection. Comparable changes in the i.p. and i.v. LD50 were observed in C57BL/6J mice. This rapid generation of protective immunity was specific for LVS, in that mice given a sublethal i.d. inoculation of LVS did not survive a lethal challenge with either Salmonella typhimurium W118 or Escherichia coli O118 BORT at any time, nor could mice given sublethal doses of S. typhimurium, E. coli, or Mycobacterium bovis BCG survive lethal doses of LVS. Although an increase in the mean time to death from S. typhimurium infection was noted when mice were given a sublethal i.d. dose of LVS 4 to 14 days earlier, no overall increase in protection or change in the S. typhimurium LD50 was observed. Thus, sublethal infection with LVS at skin sites induced rapid and specific protective immunity.